EVALUATION OF THE EFFECTIVENESS OF BISMUTH TRICALCIUM DICITRATE IN THE TREATMENT OF IRRITABLE BOWEL SYNDROME (Web of Medicine: Journal of Medicine, Practice and Nursing, 2026)
Irritable bowel syndrome (IBS) refers to functional diseases in which the pathogenesis of the development of symptoms cannot be explained by organic causes. According to modern concepts, IBS is a psychosocial disorder with impaired visceral sensitivity and intestinal motor activity, due to or lowering the pain threshold, or an increase in the intensity of the sensation of pain impulses at a normal threshold of their perception. IBS is considered one of the most common diseases of the internal organs. Among the adult population 10- 20% of individuals have relevant IBS symptoms. According to the results of most epidemiological studies, women suffer from this disease approximately 2 times more often men. The peak incidence occurs at the most active working age - from 24 years to 41 years.